Information transfer of CEO turnover: Evidence from firm-CEO mismatch - Desir, Rosemond; Seavey, Scott E.; Thevenot, Maya (Journal of Corporate Finance, 2024)
We investigate intra-industry information transfer to news of a significant corporate event, forced CEO turnover. Intra-industry information transfer occurs when announcements made by one or more firms in an industry contemporaneously affect stock prices of peer firms. We find results strongly consistent with information transfer in response to forced CEO turnover, as evidenced by significant cumulative abnormal returns for industry peer firms around the time of a turnover announcement. We further document that information transfer is stronger to turnovers that signal a firm-CEO mismatch prompted by changing industry conditions (Eisfeldt and Kuhnen 2013). Considering two moderating factors, we find weaker (stronger) information transfer when the CEO was replaced with an outsider (the announcing firm is an industry leader), providing additional evidence that forced CEO turnover at one firm can be indicative of industry-wide changes. Our study has important implications to financial analysts, investors, and boards of directors in assessing changing industry conditions in light of a forced CEO turnover at a peer firm.